Promising lines were released for irrigated lowland conditions in Bangladesh - CGIAR Research Program on Rice (2020)
Two promising lines BRRI Dhan 97 (IR83484-3-B-7-1-1-1) and BRRI Dhan99 (HHZ5-DT20-DT2-DT1) were released for irrigated lowland conditions in Bangladesh which are expected to be picked up by the seed system.